Application of Moringa oleifera Extract in Feed and Drinking Water as a Feed Additive for Broiler Chickens: A Meta-Analysis Study - Teuku Mujaddid Syahri Ar-Ridha; Samadi, Samadi; Anuraga Jayanegara (Faculty of Animal Science, Jenderal Soedirman University in associate with the Animal Scientist Society of Indonesia (ISPI) and the Indonesian Association of Nutrition and Feed Science (AINI), 2025)
Herbal plants in animal feed offers a more natural and safer alternative than synthetic antibiotics, which can lead to bacterial resistance and leave residues in poultry products. This meta-analysis study evaluated the potential of Moringa (Moringa oleifera) leaves extract as a feed additive for broiler chickens, comparing two administration methods, inclusion in feed or dilution in drinking water. Data were obtained from 29 relevant articles sourced from Google Scholar and Scopus, resulting in the analysis of 123 studies using SAS software. The results showed that administering Moringa leaves in feed significantly increased final body weight and improved feed conversion ratio (FCR), with an average FCR value of 1.92. No significant effects (P>0.05) on were identified in Moringa-boost drinking water. The average final weight of chickens given Moringa in feed compared to in drinking water was 2.09 kg vs. 2.04 kg. The carcass yield from Moringa extract in feed compared to drinking water was 71.11% vs. 78.35%. Conclusively, solid Moringa leaf extract at a dose of 0.71–1.04% is a more effective feed additive because higher dosages induce anti-nutritional factors like tannins and saponins that reduce performance. This finding offers a valuable reference for farmers to utilize local resources in cost-effective and eco-friendly way to enhance broiler chicken production efficiency.